Uji Toksisitas Letal Cr6+ Terhadap Ikan Nila (Oreochromis niloticus) - Nanik Mustikaning Tyas; Djamar Tumpal Floranthus Lumban Batu; Ridwan Affandi (Institut Pertanian Bogor, 2016)
Chromium is a risk pollutant through their carcinogenic character non degradable by organisms and accumulate into the environment. The aims to find LC50-96h of chromium on test organism. The test organism used are Oreochromis niloticus, these organisms may represent the actual condition of the environment. This study was divided into 2 steps i.e. basic and lethal toxicity (LC50-96 h) tests, being run in triplicates. Lethal toxicity test data were probity analyzed. The result showed that LC50-96h of Cr6+ on Oreochromis niloticus was 61.2 ppm.